Sex and region-specific disruption of autophagy and mitophagy in Alzheimer’s disease: linking cellular dysfunction to cognitive decline - Aida Adlimoghaddam; Fariba Fayazbakhsh; Mohsen Mohammadi; Zeinab Babaei; Amir Barzegar Behrooz; Farhad Tabasi; Teng Guan; Iman Beheshti; Mahmoud Aghaei; Daniel J. Klionsky; Benedict C. Albensi; Saeid Ghavami (Cell Death Discovery)
Abstract Macroautophagy and mitophagy are critical processes in Alzheimer’s disease (AD), yet their links to behavioral outcomes, particularly sex-specific differences, are not fully understood. This study investigates autophagic (LC3B-II, SQSTM1) and mitophagic (BNIP3L, BNIP3, BCL2L13) markers in the cortex and hippocampus of male and female 3xTg-AD mice, using western blotting, transmission electron microscopy (TEM), and behavioral tests (novel object recognition and novel object placement). Significant sex-specific differences emerged: female 3xTg-AD mice exhibited autophagosome accumulation due to impaired degradation in the cortex, while males showed fewer autophagosomes, especially in the hippocampus, without significant degradation changes. TEM analyses demonstrated variations in mitochondrial and mitophagosome numbers correlated with memory outcomes. Females had enhanced mitophagy, with higher BNIP3L and BCL2L13 levels, whereas males showed elevated BNIP3 dimers. Cognitive deficits in females correlated with mitochondrial dysfunction in the cortex, while in males, higher LC3B-II levels associated positively with cognitive performance, suggesting protective autophagy effects. Using machine learning, we predicted mitophagosome and mitochondrial numbers based on behavioral data, pioneering a predictive approach to cellular outcomes in AD. These findings underscore the importance of sex-specific regulation of autophagy and mitophagy in AD and support personalized therapeutic approaches targeting these pathways. Integrating machine learning emphasizes its potential to advance neurodegenerative research. Sex-specific differences in autophagy and mitophagy regulation in Alzheimer’s disease (AD) are highlighted. Female 3xTg-AD mice show autophagosome accumulation and cognitive deficits, while males exhibit variations in mitophagy markers and behavior.